Mangrove Conservation in East Java: The Ecotourism Development Perspectives - Hakim, Luchman; Siswanto, Dian; Makagoshi, Nobukazu (Journal of Tropical Life Science, 2017)
An analysis of the role of mangrove ecosystems in tourism was undertaken in order to build a strategy for mangrove conservation and conceptualize sustainable mangrove-based tourism development in East Java, Indonesia. The results of the present study suggest that mangroves could be used as nature-based tourism destinations. While tourism in mangrove areas in East Java clearly contributes to mangrove conservation, it still lacks a mangrove tour program, in which it is important to deliver the objectives of ecotourism. For the sustainable use of mangrove biodiversity as a tourist attraction, it is essential to know the basic characteristics of mangroves and establish mangrove tourism programs which are able to support a conservation program. It is also crucial to involve and strengthen the participation of local communities surrounding mangrove areas. The involvement of local wisdom could increase the sustainability of mangrove ecosystems.